Strategie dialogiczne według Waltera Onga SJ - Obirek, Stanisław (Horyzonty Wychowania, 2017)
Walter Ong, an American Jesuit and lecturer at Saint Louis University was quite early recognized as the author of innovative conceptions devoted to language and interpersonal communication. According to Ong, regardless of existing contradictions and differences, „man is created to unite humanity”. Such attitude to man, such optimistic anthropology, forces him to view the lack of interpersonal understanding as a transitory phenomenon Indeed, in his opinion, dialogue is not a matter of pragmatic tactics or necessity defined by the pluralistic society. Owing to dialogue, man becomes himself, becomes simply a person: „Essentially, from certain perspective the whole human life is simply a dialogue with other people and with God. Human life can be determined by means of joining in this dialogue”. This article aims only at drawing attention to the dialogue dimension of Walter Ong’s thought, which constitutes an important, though only fragmentary dimension of his activity. Matter-of-fact and objective, based on the analysis of facts, the analysis of human word leads to a conclusion that understanding among people is not only possible, but just inalienable if humankind wants to survive. At the same time, religious or attitude divisions seem secondary in the face of fundamental consideration of condition humaine.